Motivasi Siswa Terhadap Kegiatan Pengembangan Diri Seni Tari Di SMP- SDI Silungkang - Siti Nurhayati; Zora Iriani; Darmawati Darmawati (FBS Universitas Negeri Padang, 2019)
This article aimed to reveal and describe students' motivation towards dance self-development activities in SMP-SDI Silungkang. The type of this research was qualitative research with descriptive methods. The objects in the study were 22 female students and 1 male of class VII and VIII in odd semester 2018/2019 academic year. All of the objects participated self-development. The instruments used in this study were the researchers herself and free interviews. The types of data in this research were primary and secondary data. Data collection techniques were carried out by means of library research, observation, interviews, and documentation. The techniques of data analysis were carried out by the steps of data collection, data reduction, data presentation and conclusion drawing. The results showed that the motivation of students towards the self-development activities of dance in SMP of Islamic Business School (SDI) Silungkang was still quite good and the implementation of self-development in dance was running well. This school was still facing obstacles in developing dance self-development activities, such as infrastructures that were not yet complete. However, there were also several types of rewards given by the teacher to motivate students in the self-development activities. Thus, it was concluded that students 'motivation towards the self-development activities of dance in SMP of Islamic Trading School (SDI) Silungkang is quite good and needed some improvement in terms of students' external motivation, especially in the aspects of facilities and infrastructures